Modelos para estimar exigências nutricionais de aminoácidos e resposta à ingestão de metionina: sistema tradicional por fases x nutrição de precisão - Remus, Aline [UNESP] (2015)
The aim of this dissertation is to support the first steps to develop a new method to estimate methionine nutritional requirements for the pigs fed individually. The first step of this dissertation was perform a meta-analysis in order to study the response of pigs fed with different types of methionine and to quantify the ideal ratio of methionine: lysine for piglets from the initial phase to termination. The database consisted of 41 papers. To determine the methionine: lysine ratios, 83% of papers in the database were excluded because they did not meet the pigs requirement for lysine. For analysis of methionine sources were used 21 papers from initial phase, and it had no difference (P <0.05) between L-methionine, DL-methionine and methionine hydroxy-analogue. The minimum methionine: lysine ratio found was 26% methionine inclusion in function of lysine requirement. In sequence was performed a simulation study using factorials models used in pig farming (Brazilian tables of nutritional requirements for pigs and poultry (BT) and the NRC 2012), in order to compare them with the model Automatic and intelligent Precision feeder (AIPF). Data from 36 pigs were used with initial body weight of 25 kg for a period of 28 days. Body weight, feed intake and average daily gain were standardized. It was concluded that the NRC and BT models were calibrated to estimate the maximum response requirements of the population, thus overestimate the average pig requirement in more than 13%. In addition, the requirement of using an average pig in the middle of the feeding phase to estimate the requirements of a population, is a practice which must be handled with care. This is due to the wide variation in nutritional requirements that exist between the pigs from the same population. Finally the AIPF and BT models were used in a trial. The pigs were arranged in a randomized design, 2x3 factorial randomized design: two feeding programs (individual daily ...